Análise de parâmetros ecológicos sob influência da remoção da biomassa aérea de Hedychium coronarium J. KÖNIG (ZINGIBERACEAE) e enriquecimento do solo - Mattos, Lilian Aparecida Arantes de (Universidade Federal de São Carlos, 2022)
Plants with clonal growth are characterized by the vegetative production of numerous descendant individuals, called ramets, which can cover extensive natural areas, becoming independent and interconnected through internodes in rhizomes, leading to the formation of large and long-lasting clonal systems (Price and Marshall 1999). The maintenance of these systems is facilitated by the ability of clonal species for physiological integration (i.e., the ability to share resources such as water, carbohydrates and mineral nutrients between interconnected ramets) (Campoy, 2017). The plant Hedychium coronarium J. König (Zingiberaceae) is a rhizomatous macrophyte native to Asia widely distributed in Brazil, mainly in riparian areas and in ombrophilous forests. The management of this species requires specific control strategies, as this species tolerates different abiotic conditions in wetlands and presents an efficient clonal growth, resulting in large aboveground biomass production. Therefore, the objective of this work was to investigate the influence of successive mechanical cuts and soil enrichment with nitrogen (N) over time on yield patterns, starch storage in the rhizomes and growth of H. coronarium. We found a negative effect of aboveground biomass removal on biomass production, showing that aboveground biomass removal can contribute to the control of the species over time, regardless of soil enrichment with N. We also observed a compensation mechanism and decrease in reserves of starch in the rhizome and in the growth of the ramets along the mechanical cuts, showing that the reduction of the energy reserve of the plant can be a management strategy for this plant.
Analysis of ecological parameters under the influence of aerial biomass removal of Hedychium coronarium J. KÖNIG (ZINGIBERACEAE) and soil enrichment
Keywords: Plantas invasoras; Mata ripária; Ecologia de invasoras; Controle de invasor; CIENCIAS BIOLOGICAS::ECOLOGIA